1968
DOI: 10.1126/science.161.3848.1346
|View full text |Cite
|
Sign up to set email alerts
|

L-Lactic Acid: A Mosquito Attractant Isolated from Humans

Abstract: L-Lactic acid was the major component in material isolated from humans that was active as an attractant for female yellow fever mosquitoes, Aedes aegypti (L.). The L(+)-isomer was several times as attractive as the D-isomer. Good correlation was found between the attractiveness of an individual to mosquitoes and the quantity of lactic acid present in an acetone washing of his hand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
150
2
6

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(173 citation statements)
references
References 5 publications
5
150
2
6
Order By: Relevance
“…This volatile is emitted by vertebrates and has been detected on human skin (Acree et al, 1968;Bernier et al, 2000). LA was demonstrated to be the major component of perspiration (Braks et al, 1999), excreted at concentrations between 0.5 and 5mgml -1 (Eiras and Jepson, 1991;Cork and Park, 1996;Geier et al, 1996).…”
Section: Conditioning Proceduresmentioning
confidence: 99%
“…This volatile is emitted by vertebrates and has been detected on human skin (Acree et al, 1968;Bernier et al, 2000). LA was demonstrated to be the major component of perspiration (Braks et al, 1999), excreted at concentrations between 0.5 and 5mgml -1 (Eiras and Jepson, 1991;Cork and Park, 1996;Geier et al, 1996).…”
Section: Conditioning Proceduresmentioning
confidence: 99%
“…Acree et al, 1968;Dekker et al, 2005) in combination with other host-related odours such as LA and OCT (Takken et al, 1997;Geier and Boeckh, 1999;Dekker et al, 2002). These responses can be modulated by their individual experience, but mosquitoes can also associate odorants that were initially neutral, or non-attractive, with a successful feeding event.…”
Section: Consequences Of Learningmentioning
confidence: 99%
“…Bar-Zeev et al (1977) summarised the available information on the factors that appeared to attract Aedes aegypti to humans. They also carried out laboratory studies on responses to carbon dioxide, relative humidity, temperature and emanations from a human forearm, and confirmed the attractancy of [S]-lactic acid (Acree et al, 1968; Smith et al, 1970). More recently Kusakabe & Ikeshoji (1990) found that lactic acid, heat, black colour, movement and sound were all to some degree attractive to both sexes of Aedes aegypti but carbon dioxide was not attractive.…”
mentioning
confidence: 99%